👤

1.
a. 2√3+4√5=
b. 2√5+5√3=
c. 6√3+√5=
a+b+c=?
2.
11+(-2√2)+(-6√2)-4=
3.
a. 3√5+√45-20=
b. √5-√80=
a+b=?
dau coroana va rog ​


Răspuns :

Răspuns:

Explicație pas cu pas:

1.

a. 2√3+4√5

b. 2√5+5√3

c. 6√3+√5

a + b + c =  2√3 + 4√5 + 2√5 + 5√3 + 6√3 + √5

              =  13√3 + 7√5

2.

11 + ( -2√2 ) + ( -6√2 ) - 4 =

11 - 2√2 - 6√2 - 4 =

- 8√2 + 7

3.

a. 3√5+√45-20 =  3√5 + 3√5 - 20

b. √5-√80 = √5 - 4√5

a + b = 3√5 + √45 - 20 + √5 - √80

         = 3√5 + 3√5 - 20 + √5 - 4√5

         = 3√5 - 20